Polymerizable dielectric material - Sparrowe,D; Mcculloch,I; Heeney,M; Shkunov,M (2007)
The present invention relates to a novel polymerizable dielec. material comprising crosslinkable org. amine derivs. and crosslinked polymers obtained thereof, which are useful for the manuf. of dielec. layers of electronic devices, to a novel method for the manuf. of dielec. layers of electronic devices, and to electronic devices obtained by said method.